The EGFR/ErbB inhibitor neratinib modifies the neutrophil phosphoproteome and promotes apoptosis and clearance by airway macrophages - Herman, Kimberly D.; Wright, Carl G.; Marriott, Helen M.; McCaughran, Sam C.; Bowden, Kieran A.; Collins, Mark O.; Renshaw, Stephen A.; Prince, Lynne R. (Frontiers in Immunology, 2022)
Dysregulated neutrophilic inflammation can be highly destructive in chronic inflammatory diseases due to prolonged neutrophil lifespan and continual release of histotoxic mediators in inflamed tissues. Therapeutic induction of neutrophil apoptosis, an immunologically silent form of cell death, may be beneficial in these diseases, provided that the apoptotic neutrophils are efficiently cleared from the tissue. Previous research in our group identified ErbB inhibitors as able to induce neutrophil apoptosis and reduce neutrophilic inflammation both in vitro and in vivo. Here we extend that work using a clinical ErbB inhibitor, neratinib, which has the potential to be repurposed in inflammatory diseases. We show that neratinib reduces neutrophilic migration to an inflammatory site in zebrafish larvae. Neratinib upregulates efferocytosis and reduces the number of persisting neutrophil corpses in mouse models of acute, but not chronic, lung injury, suggesting the drug may have therapeutic benefits in acute inflammatory settings. Phosphoproteomics analysis of human neutrophils shows that neratinib modifies the phosphorylation of proteins regulating apoptosis, migration and efferocytosis. This work identifies a potential mechanism for neratinib in treating acute lung inflammation by upregulating the clearance of dead neutrophils and, through examination of the neutrophil phosphoproteome, provides important insights into the mechanisms by which this may be occurring.